Development of isolated Malay words speech recognition prototype using recurrent neural network / Irdhan Sarbini - Sarbini, Irdhan (2005)
In this research, a prototype of isolated Malay word speech recognition using recurrent neural network (RNN) is proposed. The research is working on speaker independent, which is combination of male and female respondent. A simple three-layer RNN which is Elman Network is employed to learn the pattern of speech features. Melfrequency Cepstral Coefficient (MFCC) feature is selected and the features are extracted by using Speech Filing System freeware application. Experiments are performed to determine the optimal number of hidden neurons for the architecture of RNN. The total recognition rate is 95 %. This research also reveals that RNN is able to give good performance for speech recognition and for incomplete data.